1999
DOI: 10.1162/evco.1999.7.3.231
|View full text |Cite
|
Sign up to set email alerts
|

The Gambler's Ruin Problem, Genetic Algorithms, and the Sizing of Populations

Abstract: This paper presents a model to predict the convergence quality of genetic algorithms based on the size of the population. The model is based on an analogy between selection in GAs and one-dimensional random walks. Using the solution to a classic random walk problem—the gambler's ruin—the model naturally incorporates previous knowledge about the initial supply of building blocks (BBs) and correct selection of the best BB over its competitors. The result is an equation that relates the size of the population wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
223
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(235 citation statements)
references
References 2 publications
7
223
0
4
Order By: Relevance
“…However, the larger population was necessary to solve the 5-bit trap problem since more samples (chromosomes) were needed to accurately cover each trap block. This observation is consistent with previous work where the necessary population size was shown to increase exponentially with the size of the trap [19,25]. Consequently, the ignorant algorithms would be likely to find the optimum solution if permitted additional fitness function evaluations by an order of magnitude or more.…”
Section: Deceptive Trap Functionssupporting
confidence: 91%
“…However, the larger population was necessary to solve the 5-bit trap problem since more samples (chromosomes) were needed to accurately cover each trap block. This observation is consistent with previous work where the necessary population size was shown to increase exponentially with the size of the trap [19,25]. Consequently, the ignorant algorithms would be likely to find the optimum solution if permitted additional fitness function evaluations by an order of magnitude or more.…”
Section: Deceptive Trap Functionssupporting
confidence: 91%
“…However, they assumed that if wrong BBs were chosen in the first generation, the GAs would be unable to recover from the error. Harik, Cantú-Paz, Goldberg, and Miller (Harik, Cantú-Paz, Goldberg, & Miller, 1999) refined the above model by incorporating cumulative effects of decision making over time rather than in first generation only. Harik et al (Harik, Cantú-Paz, Goldberg, & Miller, 1999) modeled the decision making between competing BBs as a gambler's ruin problem.…”
Section: Population-sizing Modelmentioning
confidence: 99%
“…The success of these techniques is based on the maintenance of genetic diversity, for which it is necessary to work with large populations. The population size that guarantees an optimal solution in a short time has been a topic of intense research [2], [3]. Large populations generally converge to better solutions, but they require more computational cost and memory requirements.…”
Section: Introductionmentioning
confidence: 99%
“…They further enhanced the equation which allows accurate statistical decision making among competing building blocks (BBs) [2]. Extending the decision model presented in [2], Harik et al [3] tried to determine an adequate population size which guarantees a solution with the desired quality. To show the real importance of the population size in Evolutionary Algorithms (EAs) He and Yao [5] showed that the introduction of a non random population decreases convergence time.…”
Section: Introductionmentioning
confidence: 99%